2006
DOI: 10.1007/s11187-004-5612-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Entrepreneurial Risk Assessment on Venture Launch or Growth Decisions

Abstract: Entrepreneurs are thought to engage in riskier behavior than nonentrepreneurs, yet little empirical evidence supports that intuitively appealing notion. We argue instead that differences in information, not risk aversion, may explain the decision to launch or grow a venture. We separately test risk taking propensity and risk assessment. We hypothesize that entrepreneurs will not differ from nonentrepreneurs on risk taking propensity. Additionally, we propose and test a model of risk assessment. The sample size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 26 publications
3
44
0
1
Order By: Relevance
“…Brockhaus (1980), for example, compared entrepreneurs and managers and found that risk-taking does not distinguish either one group from the other. Similar results have been found by other scholars (Masters and Meier, 1988;Norton and Moore, 2006;Palich and Bagby, 1995). In other studies, however, it has been found that risk-taking propensity is higher among entrepreneurs than among other individuals (e.g., Begley and Boyd, 1987; for a meta-analytic review, see Stewart and Roth, 2001).…”
Section: Literature Review and Research Gapsupporting
confidence: 88%
“…Brockhaus (1980), for example, compared entrepreneurs and managers and found that risk-taking does not distinguish either one group from the other. Similar results have been found by other scholars (Masters and Meier, 1988;Norton and Moore, 2006;Palich and Bagby, 1995). In other studies, however, it has been found that risk-taking propensity is higher among entrepreneurs than among other individuals (e.g., Begley and Boyd, 1987; for a meta-analytic review, see Stewart and Roth, 2001).…”
Section: Literature Review and Research Gapsupporting
confidence: 88%
“…In previous studies by one of the 11 Whether entrepreneurs are more likely to engage in risky behaviour (see Palich and Bagby, 1995) is a controversial issue and empirical evidence is inconclusive. For example, in a recent paper, Norton and Moore (2006) conclude that entrepreneurs do not differ from non-entrepreneurs as regards their risk-taking propensity.…”
Section: From Macroeconomic Outcomes To Microfoundations Of New Firm mentioning
confidence: 99%
“…Indeed, it is how the entrepreneur perceives the opportunity rather than the opportunity itself that matters (Dana and Dana, 2005). Lower risk perception may be the result of entrepreneurs framing the business situation too positively (e.g., Norton and Moore, 2006;Palich and Bagby, 1995). Willebrands et al (2012) argue that this could lead to a lack of risk mitigation.…”
Section: Related Literaturementioning
confidence: 99%
“…Most empirical studies make use of experimental designs and only look at the impact of risk perception on a single, predefined decision (Forlani and Mullins, 2000;Norton and Moore, 2006). Sitkin and Weingart (1995), for example, show that higher risk perception leads to less risky decisionmaking by entrepreneurs, but do not analyse the effect on firm performance.…”
Section: Related Literaturementioning
confidence: 99%